Development of the Halifax Visual Scanning Test: A New Measure of Visual-Spatial Neglect for Personal, Peripersonal, and Extrapersonal Space. (16th April 2019) - Whitehouse, Christiane E.; Green, Janet; Giles, Sarah M.; Rahman, Rosanna; Coolican, Jamesie; Eskes, Gail A.
Abstract : Objectives: Visual-spatial neglect is a common attentional disorder after right-hemisphere stroke and is associated with poor rehabilitation outcomes. The presence of neglect symptoms has been reported to vary across personal, peripersonal, and extrapersonal space. Currently, no measure is available to assess neglect severity equally across these spatial regions and may be missing subsets of symptoms or patients with neglect entirely. We sought to provide initial construct validity for a novel assessment tool that measures neglect symptoms equally for these spatial regions: the Halifax Visual Scanning Test (HVST). Methods: In Study I, the HVST was compared to conventional measures of neglect and functional outcome scores (wheelchair navigation) in 15 stroke inpatients and 14 healthy controls. In Study II, 19 additional controls were combined with the control data from Study I to establish cutoffs for impairment. Patterns of neglect in the stroke group were examined. Results: In Study I, performance on all HVST subtests were correlated with the majority of conventional subtests and wheelchair navigation outcomes. In Study II, neglect-related deficits in visual scanning showed dissociations across spatial regions. Four inpatients exhibited symptoms of neglect on the HVST that were not detected on conventional measures, one of which showed symptoms in personal and extrapersonal space exclusively. Conclusions: The HVST appears a useful measure of neglect symptoms in different spatial regions that may not be detected with conventional measures and that correlates with functional wheelchair performance. Preliminary control data are presented and further research to add to this normative database appears warranted. ( JINS, 2019, 25, 490–500)